HOSPITAL ADMINISTRATION IN A PERIPHERAL REMOTE LOCATION HOSPITAL: A EVIDENCE BASED STUDY - PITALE, DEVDATT LAXMAN; JADHAV, SUJATA N. (International Journal of Current Pharmaceutical Research, 2024)
Objective: The organisation of the human society has undergone a unique transition throughout the last decades. With the rise of ever growing technologization and disruptive innovations, populations also demand more social and environmental initiatives from firms and governments. In 2015, the United Nations (UN) member states agreed upon a 2030 Agenda for Sustainable Development. Developing a sustainable UHC is decisive to ensure better economic prospects and social equality across socioeconomic classes. This can be achieved by lowering the barriers to access health services to the most vulnerable groups and improve mortality and disability rates in the potential workforce. Methods: The present study was conducted in a remote location defence hospital catering to the health care needs of serving personnel of Indian armed forces and civilians residing in this peripheral area. The basic specialties including Obstetrics, paediatrics, medicine and general surgery are provided at this centre 24*7 by the dedicated medical officers of Indian Armed forces. Results: Sustainability of care continuously evolves towards becoming a major factor for public healthcare organisations, and more accountability will likely be demanded of managers to deliver on each aspect of its triple bottom line. This study shows that prevention and patient empowerment both carry great potential to attain this objective. Conclusion: It is necessary to set priorities and act according to available resources and organisational vision. The central threats to sustainability of public health care welfare systems in peripheral hospitals identified, namely the ageing population and rise in chronic diseases. UHC at a meso and micro level, could provide a much better rationale for scholars to evaluate the need for change, and contribute to draft more inclusive sustainable strategies.